Driven by the Discount Factor: Impact of Mergers on Market Performance in the Semiconductor Industry - Jeremiah Harris; Ralph Siebert (Center for Economic Studies and ifo Institute (CESifo), 2015)
This study investigates the impact of firm-specific discount factors on merger formation and market performance. We estimate firm-specific discount factors for 228 publicly traded and privately held firms operating in the semiconductor market and apply a heterogeneous treatment effects model which accounts for firms' endogenous selection into mergers, as well as the heterogeneous impact of mergers on the product market. Our study provides evidence that firms' discount factors explain merger formation and the impact on product market performance. More specifically, we find that acquiring firms characterized by high discount factors (patient firms) merge with efficient and innovative target firms, and achieve high efficiency gains. In contrast, acquiring firms characterized by low discount factors (impatient firms) merge with less innovative target firms, and achieve higher market power effects.
Keywords: D24; D43; G34; L13; L22; 330; discount factor; discount rate; dynamic oligopoly model; market performance; mergers and acquisitions; semiconductor industry